2021
DOI: 10.1002/er.6821
|View full text |Cite
|
Sign up to set email alerts
|

The effect of graphene quantum dots/ ZnS co‐passivation on enhancing the photovoltaic performance of CdS quantum dot sensitized solar cells

Abstract: The effect of graphene quantum dots (GQDs) as a passivating layer for cadmium sulfide (CdS) quantum dot-sensitized solar cell (QDSSC) has been investigated. GQDs were prepared by the liquid exfoliation method. The optical properties of GQDs were studied by UV-Vis and photoluminescence spectroscopies. The morphology of GQDs was studied by transmission emission morphology (TEM) analysis. Further, the photoexcitation behavior of GQDs has been studied in detail using emission spectroscopy and its effect on the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…[87] A lot of other similar studies where AFM played a major role in the characterization of QDSSCs have been reported. [88][89][90][91][92] Figure 4 depicts a simplified schematic of QD intermediate band solar cells. In an investigation which was focused at formulating stacks of QD with trivial strain for intermediate band solar applications, AFM was applied to facilitate the establishment of improved uniformity in QD size distribution and areal density which was accomplished through vertical ordering of the dots successively with the objective of achieving strain compensation in the dot layers.…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[87] A lot of other similar studies where AFM played a major role in the characterization of QDSSCs have been reported. [88][89][90][91][92] Figure 4 depicts a simplified schematic of QD intermediate band solar cells. In an investigation which was focused at formulating stacks of QD with trivial strain for intermediate band solar applications, AFM was applied to facilitate the establishment of improved uniformity in QD size distribution and areal density which was accomplished through vertical ordering of the dots successively with the objective of achieving strain compensation in the dot layers.…”
Section: Perovskite Solar Cellsmentioning
confidence: 99%
“…[ 87 ] A lot of other similar studies where AFM played a major role in the characterization of QDSSCs have been reported. [ 88–92 ]…”
Section: Materials Designmentioning
confidence: 99%
“…As a result, they are highly promising emerging photovoltaic devices . However, despite the theoretical power conversion efficiency of QDSSCs reaching 66%, their current practical efficiency (15%) falls far below this value, indicating substantial room for improvement. , Furthermore, they open up new potential applications in areas such as architectural glass, automotive glass, and electronic devices, thereby creating new market opportunities for solar panel deployment in these domains. …”
Section: Introductionmentioning
confidence: 99%
“…If transparent solar cell glass can be commercialized, the light that has not been converted into electricity can be used for lighting. With the increasing demand for solar cells, the investment in the research and development of new transparent QDSSCs is also increasing. , The slow development of transparent photoanodes has become a problem that must be faced. TiO 2 is a commonly used wide-band-gap semiconductor in solar cell photoanodes .…”
Section: Introductionmentioning
confidence: 99%